AKURASI DIAGNOSTIK NILAI ADC MRI DALAM MEMPREDIKSI TUMOR JARINGAN LUNAK JINAK DAN GANAS BERDASARKAN HASIL PEMERIKSAAN HISTOPATOLOGI - AMIN, ROSMINI; Ilyas, Muhammad; Muis, Mirna; Zainuddin, Andi Alfian; Johan, Muhammad Phetrus; Latief, Nikmatia (Universitas Udayana, 2023)
ABSTRACT DWI with ADC mapping adds value to conventional MRI imaging by offering assessment of cellularity functionality with the potential to help differentiate between benign and malignant lesions. The aim of this study is to assess the accuracy of the ADC value MRI in predicting soft tissue tumors benign and malignant. This study was carried out by the Radiology Installation of Wahidin Sudirohusodo Hospital from February 2020 to August 2022 with a sample of 36 people and an age range of 9-74 years. The statistical method used was to calculate the value of sensitivity, specificity, Positive Predictive Value and Negative Predictive Value to assess accuracy as well as ROC and Mann Whitney tests. The results show that it consists of 36 samples with soft tissue tumors (malignant: 25 samples and benign : 11 samples). The mean value of ADC for malignant soft tissue tumors is 0.998 ± 0.526 x 10-3mm2/s and benign is 1.705 ± 0.665 x 10-3mm2/s. With a Cut Off value to distinguish malignant and benign soft tissue tumors of 1,265 x 10-3 mm2/s, with a sensitivity of 81.8%, specificity of 80%, Positive Predictive Value 64.3%, Negative Predictive Value 90.9%, Accuracy 80.5% and AUC 0.81. The accuracy of the ADC MRI value is 80.5%, indicating that the ADC value can be used as an additional modality to help predict benign and malignant soft tissue tumors. Keywords: Soft tissue tumor, MRI, DWI, ADC, Histopathology